Developing ecological protection redline policy for land use pattern optimization in the typical black soil region of Northeastern China - Chen, Yu; Zhao, Xinyu; Wu, Song; Tong, Zhiqiang (Frontiers in Environmental Science, 2024)
Typical black soil regions in Northeastern China (TBSN) are facing problems of degradation of ecosystem services (ESs) and spatial conflicts between cropland and ecological land. Ecological Protection Redline (EPR) policy is one of the first national policies to utilizing multiple ESs. However, there is no standardized framework of delineation and validation for TBSN. In this study, the framework of Ecological Protection Redline delineation was further improved in three aspects of the ecosystem, namely, service function, ecological sensitivity, and biodiversity. Specifically, the framework considered the conflict between high-quality cropland and ecological land in the TBSN. We examined EPR effectiveness by comparing ESs and trade-off/synergistic relationships of different land use scenarios for 2035. The results show that 1) the EPR delineation threshold for each key indicator was determined to be 15%, considering the quality level of cropland. The ecological redline area of 89,593.63 km2 was identified, which was concentrated in the southwestern part of the Mengdong typical black soil subzone and Songnen typical black soil subzone. 2) Compared to the current ecological protection scenario and current ecological protection redline scenario, the optimized EPR scenario was the best solution to guarantee the sustainable development of the TBSN, maximizing ESs, weakening trade-offs, and strengthening synergistic relationships between them. The results of the study provided a theoretical basis for land use planning and the scientific management of ecosystems in the TBSN.